Level of Knowledge and Participation of the Young Generation in Waste Management - Ratnawati, Beata; Dellarosa, Luvy; Jannah, Nurul; Paramitadevi, Yudith Vega; Silaban, Intan Roulina; Hidiya, Miesriany; Ridwan, Wonny Ahmad; Budiharto, Ivone Wulandari; Suri, Wiranda Intan; Prasetya, Dimas Ardi; Tunggadewi, Andini Tribuana; Wahdi, Emil; Meliana, Linda; Luthfiyah, Nanda Amirah; Widiawati, Yesi Eka; Natalia, Adelisa (Riwayat: Educational Journal of History and Humanities, 2024)
Waste has become a problem in city/regency. The waste produced originates from daily activities. The study was conducted between June and October. The aim of this research was to analyze the level of knowledge and participation of students as the younger generation in waste management. Data were obtained using questionnaires administered to 177 young participants. The obtained data were descriptively analyzed. The results showed that 87% of the students knew the importance of processing the waste produced so as not to pollute the environment. However, only 32% had processed waste. The processing includes converting organic waste into compost or eco-enzymes.